Forensic feed strategy: Incorporation of multivariate and instrumental analyses for authentication of fish feed sources - Idris, Mohamed Haniff Hanafy; Abdullah Sani, Muhamad Shirwan; Hashim, Amalia Mohd; Mohd Zaki, Nor Nadiha; Abdul Manaf, Yanty Noorzianna; Yuswan, Mohd Hafis; Mohd Desa, Mohd Nasir; Arshad, Syariena; Hassan, Mohd Sukri; Yusof, Yus Aniza; Kamaruddin, Mohd Salleh; Mustafa, Shuhaimi (HH Publisher, 2022)
This study authenticated fish feed sources and determined lard adulteration using dataset pre-processing, principal component analysis (PCA), discriminant analysis (DA) and partial least square regression (PLSR) on 19 triacylglycerols (TAGs) and 16 thermal properties (TPs). At cumulative variability (90.625%) and Keiser-Meyer Olkin (KMO) value (0.811), the PCA identified 10 TAGs and 3 TPs with strong factor loading. The dioleoyl-1-palmitoyl glycerol (POO) dipalmitoyl-3-oleoyl glycerol (PPO) and dipalmitoyl-1-linoleoyl (PPL) characterized fish feeds containing palm oil while dilinoleoyl-1-oleoyl glycerol (OLL), dilinoleoyl-1-palmitoyl (PLL), dioleoyl-3-linoleoyl glycerol (OOL), initial cooling temperature (ICT), palmitoyl-oleoyl-linoleoyl glycerol (POL), palmitoyl-stearoyl-oleoyl glycerol (PSO) and final heating temperature (FHT) characterized lard-containing fish feeds. The DA had successfully classified the fish feed sources and selected the PPL, POL, PPO, OOL, ICT, PLL, FHT, POO and OLL as the most influential biomarkers for the authentication purpose. The T-test result (p > 0.05) indicated that the PLSR could determine the percentage of lard adulteration in fish feed. Hence, incorporating multivariate and instrumental analyses could authenticate the fish feed sources.